Assessing needs of family members of inpatients with advanced cancer - Bužgová, R; Špatenková, N; Fukasová-Hajnová, E; Feltl, D (European journal of cancer care, 2016)
To provide high-quality and effective cancer care, problems and unmet needs of family members during their relatives' hospitalisation have to be identified as well. The aims were to determine how needs of family members of patients with terminal cancer are met and to analyse factors that influence them. The needs were assessed with the Family Inventory of Needs. Each item (n = 20) represents one need of family members, for which the importance and satisfaction are rated. The study comprised 270 family members of hospitalised advanced cancer patients staying in the University Hospital Ostrava who were receiving palliative care. The family members preferred sufficient basic information and patient comfort. The unmet needs were support of hope (73%) and provision of information (65%). The unmet needs were more frequently identified by women, individuals with lower education, younger persons, unemployed, patients' children and family members of patients with generally unfavourable health status (P < 0.05). There was a correlation between lower quality of life and higher numbers of unmet needs. Targeted interventions aimed at meeting important needs of the family members may improve their quality of life.
Keywords: dospělí; Palliative Care; Female; rodina; Needs Assessment; paliativní péče; osobní uspokojení; Adult; ženské pohlaví; průřezové studie; Neoplasms; odhad potřeb; nádory; family members; lidé; Inpatients; Personal Satisfaction; support; end of life; Aged, 80 and over; hospitalizace; needs; Cross-Sectional Studies; Male; Aged; Hospitalization; Family; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; hospitalizovaní pacienti; palliative care; Humans